Multimedia Interaktif dengan Storyline Sebagai Media Pembelajaran Bahasa Indonesia - Nugraha, Tria Aditia; Suharno; Setiawan, Hafis Ramadhan (Jurnal Pendidikan dan Pengajaran, 2024)
This study aims to develop and evaluate interactive learning media based on Articulate Storyline 3 to support Indonesian language learning for 10th grade high school students, especially in the Observational Text Report material. The methodology used is Research and Development (R&D) with the ADDIE development model consisting of five stages: analysis, design, development, implementation, and evaluation. The resulting learning media is designed to improve students' understanding through structured materials and interactive quizzes that can be accessed via an Android application. The results of the study indicate that this learning media is effective in improving students' understanding of the structure and language features of observational text reports. Users provide positive feedback on the design and interactive features of this media. However, the study also identified several areas for improvement, such as adding variations of questions and improving visual quality. Thus, this learning media is expected to be an innovative alternative in supporting a more flexible and adaptive teaching and learning process in the digital era.